Corporal punishment and violent behavior spectrum: a meta-analytic review - Pan, Qingna; Chen, Siru; Qu, Ying (Frontiers in Psychology, 2024)
Corporal punishment is believed to precede various forms of violent behavior, yet prior research has yielded inconsistent findings, partly due to variations in violent types and other factors. This meta-analysis systematically reviewed 35 studies including 144 effect sizes (comprising a total sample size of 159,213) investigating the association between corporal punishment and a spectrum of violent behaviors called Violent Behavior Spectrum (VBS). Additionally, meta-regressions were conducted to explore the moderating impact of punishment severity, violence type and cultural context. Our findings indicated a significant positive relationship between corporal punishment and VBS (r = 0.238, 95%, CI [0.176, 0.300]). Notably, punishment severity was found to influence the strength of this association. Namely, The more severe the corporal punishment, the more likely it is to lead to VBS. These results enhance our understanding of the intricate connection between corporal punishment and various forms of violence, providing valuable insights for both parenting practices and policy development.